The influence of mensturation on training schedules in well-trained and elite female mountain bike, road and cyclocross athletes - Aitkenhead, R.; Kirkwood, L.; Florida-James, G.; Ingram-Sills, L. (Journal of Applied Sports Sciences, 2023)
Female physiology is unique and driven by fluctuations in sex hormones that regulate the menstrual cycle. These hormones present myriad mechanisms that may influence physiological systems, potentially implicating exercise per formance. However, research exploring the MC in athletes is limited. This study investigated if training status (well-trained/elite) influenced MC-related symptoms, training schedules, sleep quality, arousal, and alertness of elite and well trained female mountain bike, road, and cyclocross athletes. Fifteen well-trained (n= 7) and elite (n= 8) cyclists (age: 29 ± 7yrs, height: 1.7 ± 0.1m, body mass: 61.9 ± 7.7kg) tracked their MC symptoms, basal body temperature, body mass, sleep, arousal, and alertness measures daily for three months. The MC was split into two phases, follicular and luteal, and participants were provided ovulation kits to identify the phases. The most reported symptoms were fatigue, bloating, abdominal pain, and cramping. Athletes` BBT was significantly greater (p<0.05) in the LP compared to the FP (0.4 ºC, p=0.01, d=0.4). No significant differenc es (p>0.05) in body mass, sleep duration and quality, alertness and arousal were observed between well-trained and elite athletes. Further, no significant differences between statuses for any training variables, average or maximum heart rate, training load (bTRIMP), average or maximum speed, and rate of perceived exertion were observed. The MC did not influence physiological re sponses and training variables in well-trained and elite mountain bike, road, and cyclocross female athletes. Nevertheless, individual fluctuations were present, and it is recommended that athletes monitor their own MC to optimize training and ultimately performance.